2013
DOI: 10.1093/jxb/ert243
|View full text |Cite
|
Sign up to set email alerts
|

Mn tolerance in rice is mediated by MTP8.1, a member of the cation diffusion facilitator family

Abstract: Manganese (Mn) is an essential micronutrient for plants, but is toxic when present in excess. The rice plant (Oryza sativa L.) accumulates high concentrations of Mn in the aerial parts; however, the molecular basis for Mn tolerance is poorly understood. In the present study, genes encoding Mn tolerance were screened for by expressing cDNAs of genes from rice shoots in Saccharomyces cerevisiae. A gene encoding a cation diffusion facilitator (CDF) family member, OsMTP8.1, was isolated, and its expression was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
134
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(152 citation statements)
references
References 51 publications
9
134
1
1
Order By: Relevance
“…6). Mn specificity and vacuolar localization were recently also demonstrated for MTP8 orthologs in cucumber (Cucumis sativus; Migocka et al, 2014) and rice (Oryza sativa; Chen et al, 2013). The function of MTP8 to sequester Mn into vacuoles, therefore, is widely conserved across species, with the possible exception of barley (Hordeum vulgare), where MTP8 homologs have been localized to the Golgi apparatus (Pedas et al, 2014).…”
Section: Arabidopsis Mtp8 Is a Vacuolar Mn Transporter In Rootsmentioning
confidence: 94%
“…6). Mn specificity and vacuolar localization were recently also demonstrated for MTP8 orthologs in cucumber (Cucumis sativus; Migocka et al, 2014) and rice (Oryza sativa; Chen et al, 2013). The function of MTP8 to sequester Mn into vacuoles, therefore, is widely conserved across species, with the possible exception of barley (Hordeum vulgare), where MTP8 homologs have been localized to the Golgi apparatus (Pedas et al, 2014).…”
Section: Arabidopsis Mtp8 Is a Vacuolar Mn Transporter In Rootsmentioning
confidence: 94%
“…These two proteins have also been shown to localize and function in similar patterns to those Mtp11 proteins (Erbasol et al, 2013). Finally, in a very recently published study, researchers identified OsMTP8.1, which is the rice homolog of AtMTP11, and reported that OsMTP8.1 confers manganese tolerance via vacuole sequestering of the same element (Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 88%
“…Recent studies on manganese tolerance clearly show the robustness of cDNA library based studies to identify heavy metal detoxification genes in plant species (Chen et al, 2013;Erbasol et al, 2013;Papoyan and Kochian, 2004;Pence et al, 2000). Apart from that, these studies have also shown the evolutionary importance and convergence of the secretory pathway proteins' significant involvement on the heavy metal detoxification (Chen et al, 2013;Erbasol et al, 2013;Peiter et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of OsMTP8.1, a member of the cation diffusion facilitator family, tended to be greater in OX5 than in null plants as well. OsMTP8.1 localizes to the tonoplast of leaf cells and appears to be important for loading Mn into the vacuole, since it is induced by Mn toxicity (Chen et al, 2013). Other transporters encoded by OsYSL6 and OsMTP9 have been shown previously not to change expression with Mn supply (Sasaki et al, 2011;Ueno et al, 2015).…”
Section: Ox Lines Showed Increased Expression Of Mn Transportersmentioning
confidence: 99%